FAKTOR – FAKTOR YANG MEMPENGARUHI KEUNGGULAN BERSAING DALAM UPAYA MENINGKATKAN MARKET SHARE - Apriliani, Lydia; Ferdinand, Augusty Tae (Faculty of Economics and Business Diponegoro University, 2015)
The study aims to analyze the market share of the competitive advantage of the iPhone smartphone in mobile phone sales agents in Semarang. This study departs from the research problem is: